PENGARUH PENGETAHUAN AKUNTANSI, TINGKAT PENDIDIKAN, LATAR BELAKANG PENDIDIKAN DAN MOTIVASI KERJA TERHADAP PENGGUNAAN INFORMASI AKUNTANSI PADA PELAKU UMKM DI KOTA BIMA - NURHIKMAH, NURHIKMAH; BAMBANG, BAMBANG; NURABIAH, NURABIAH (GANEC SWARA, 2024)
This study aims to examine the effect of accounting knowledge, education level, educational background and work motivation on the use of accounting information on MSME actors in Bima City. This research is quantitative associative research. This study uses primary data obtained by distributing questionnaires to 137 respondents who are owners/ managers of MSMEs in Bima City. The data analysis technique in this study was carried out using the Partial Least Square (PLS) method using SmartPLS 3.0 software. The result of this study is that there is a positive influence between accounting knowledge and work motivation on the use of accounting information. However, the level of education and educational background has no significant effect on the use of accounting information. This research is limited to accounting knowledge, education level, educational background and work motivation so that other variables need to be developed to be more in-depth such as business age, business scale, accounting training, business experience and others.